INTEGRASI NILAI-NILAI NASIONALISME DALAM PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN INTERDISIPLINER - Durhan Durhan (Fakultas Agama Islam Universitas Islam Madura, 2020)
Islamic Religious Education is a compulsory subject that needs to be given to students every week. In learning Islamic religious education, educators more often use the lecture method in the learning process. So that the learning process in the classroom, students do not really respond in any given material, the reason, this learning is not creative and innovative. The material cannot be separated from good and bad or halal and haram. Submission of such materials is always delivered in conventional ways. Therefore, in this research, Islamic religious education is innovated by integrating nationalism values ​​with an interdisciplinary approach. So, this formula includes: 1) how to understand the values ​​of nationalism and Islamic Education, 2) how to approach Islamic Religious Education with Interdisciplinary in Islamic Religious Education subjects. the purpose of this study is that Islamic education is not only valued as education that only kneels in the religious realm. In this study the approach used is a qualitative approach. This research is in the form of library research in which the material and source of data tracking are focused on articles, journals, books and other literature that are still related to this research. The ones used are content analysis and descriptive analysis. The results of this study are; 1) the students understand the values ​​of nationalism and Islamic Education; 2) students understand the Interdisciplinary approach in Islamic Religious Education subjects.